Spatial Distribution and Species Diversity of Marine Bibalves Along the Rocky Intertidal Zone of Veraval, Gujarat, India. - Rahul B. Solanki 1*; Jatin V. Raval 2 (International Journal of Marine Life, 2026)
The rocky intertidal shoreline of Veraval, located along the Saurashtra coast of Gujarat, serves as a vital habitat for various marine organisms due to its unique composition of rocky- sandy patches and tidal pools. This study was undertaken to evaluate the diversity and spatial distribution of marine bivalves at the Jaaleshwar coast (20º 54’ 36.210’’ N, 70º 21’ 09.090’’ E). Field observations were carried out over nine months from July 2020 to March 2021. To ensure a comprehensive assessment, a quadrat sampling technique (0.25 m 2 ) was employed in a zig-zag pattern across the vertical intertidal zones during low tide periods. Our findings recorded a total of 8 bivalve species representing 5 families and 5 orders. Among these, the 2 family Veneridae emerged as the most dominant, showcasing the highest diversity index of 47.36 and a mean density of 1.0. On the other hand, families such as Ostreidae and Lucanidae showed minimal presence. The data clearly indicates a seasonal trend, where the maximum population density was observed during the Monsoon, likely due to optimal environmental conditions, while the lowest density was noted in Summer. Furthermore, the study noted that human-induced activities like port operations, fisheries, and waste disposal are increasingly putting pressure on this fragile ecosystem. These results underline the importance of consistent ecological monitoring to preserve the malacofauna of the Veraval coast.
Keywords: Intertidal Zone; Keywords: Bivalves; Veraval Coast; spatial distribution; species diversity